Sustainable Ecotourism Education: Empowering Local Communities: Pendidikan Ekowisata Berkelanjutan: Memberdayakan Masyarakat Lokal - Ridhani, Delia Triscahya; Ariani, Suci; Satria, M Zufar Hanan; Hidayah, Dwi Larasati Kharismatul; Zahro, Nafidatul; Hadi, Muhammad Ikhsan; Nugraha, Ahmad Ardiansyah; Asrofi, Maulana Muhammad; Roiuddin, Moch; Wulandari, Tri; Drmarini, Aulia Rahma; Dianita, Pramesty Ardea Nur; Annida, Adilatul Bilqos; Nisa, Arienta Wardatun; Jannah, Nur Aini Miftakhul; Nurshanty, Dinda Dinianti; Rosyidah, Ni’matur; Murdiani, Putri Setya Ayu; Firdausi, Salsabila; Hanim, Denysa Firda; Prasetyo, Muhammad Aldi Awi; Pangestu , Eka Adji Setya; Rokhania , Atik; Rahmawati, Fita Widi (Proceedings of The ICECRS, 2023)
The aim of this service is to provide local communities with education and training on ecotourism topics such as environmental management, tour guides and sustainable practices. The service method used is a participatory approach by involving the community in planning and implementing the program so that they feel responsible for sustainable ecotourism initiatives. The result of this service is an increase in environmental awareness, namely awareness of the importance of protecting the natural environment, making people behave better. This dedication produces implications in the form of a sustainable development model, meaning a model that can be used in other places to encourage sustainable community development and ecotourism. Therefore, it is hoped that this service will increase the responsibility and independence of local communities while generating positive economic and environmental impacts in the long term. Highlight: Community Involvement: Engaging locals in program planning fosters a sense of responsibility for sustainable ecotourism initiatives. Environmental Awareness: Resulting in increased awareness and better behaviors towards protecting the natural environment. Sustainable Development Model: Creating a replicable model for sustainable community development and ecotourism, benefiting other areas in the long term. Keyword: Ecotourism, Ecology, Sustainable Ecotourism